The Interactive Video Models in Developing Toilet Training Skills for Elementary Students - Khairatun Nisa; Sholihatul Hamidah Daulay (Universitas Pahlawan Tuanku Tambusai, 2022)
Currently, learning content that is more tangible and easily understood by students is learning by using media. The purpose of this research is to prioritize the needs that refer to the level of achievement standards in the form of stimulation or skills of elementary school students in toilet training habituation with correct ethics. The method used is an innovative working method. The researcher invited 10 students to be tested through interviews containing 10 questions about aspects of toilet training skills. Based on the results of interview assessments and practice trials on toilet training videos, there are very satisfactory results, namely, 90% of students are declared very good and some of the students are good, so it can be concluded that learning by using video media is feasible to be used or tested on students. This innovative research resulted in a product in the form of an interactive video CD entitled